Fibromatous plaques of the forehead and scalp: a clue to the diagnosis of tuberous sclerosis. - Patrizi, A.; Neri, I.; Passarini, B.; Parmeggiani, A. (European Journal of Pediatric Dermatology, 2018)
Tuberous sclerosis is usually diagnosed thanks to three classical signs, namely epilepsy, mental retardation and angiofibromas. Among the cutaneous signs of the disease the Authors underline the importance of the fibromatous plaques. As a matter of fact, even rare, the fibromatous plaques are sometimes precocious and represent a clue to the diagnosis of fibrous sclerosis. 2 infantile cases of tuberous sclerosis are reported. Besides the typical manifestations of the disease, the two children presented a fibromatous plaque, which was respectively localised on the forehead and scalp.